Representasi Prestasi Atlet Maraton dalam Unggahan Instagram @adidasrunning Bertajuk “History in Time” - Haidar Nugroho Dwifandi; Rahardian Shandy Ekohandito (CV. ITTC INDONESIA, 2026)
Maintaining a strong identity is essential for a brand like Adidas to ensure consistency in its marketing communication strategy, especially on social media. Through its Instagram account, @adidasrunning, Adidas aims to uphold its identity by creating meaning through narratives and visual representations featured in its marketing campaigns. One of the campaigns is titled